Perubahan Persentase Unsur Hara Serasah Akibat Proses Dekomposisi Pada Empat Spesies Tanaman Gugur Daun di Kebun Raya Purwodadi - Darmayanti, Agung Sri; Rindyastuti, Ridesti (JURNAL BIOLOGI INDONESIA, 2012)
Percentage changes of litter nutrient due to decomposition process of four deciduous plant species in Purwodadi Botanic Garden. The nutrient release pattern of plant litter is different among species. Decomposition and nutrition release of organic material was observed in four species Swietenia macrophylla, Lagerstroemia speciosa, Ficus benjamina and Kigelia Africana in Purwodadi Botanic Garden. Litter mass was measured and chemical compositionwas analized including poliphenol, celulose, lignin, carbon (C), Nitrogen (N), C/N ratio, phospor (P), and Kalium (K) during 3 months. Litterbag method was applied in this research. Freshlitters were brought into bag and placed in the forest floor. Litterbag and litter chemical monitoring was established once a week. The research result showed that C ratio of four species in early phase increase then decrease in late phase of incubation and significantlydifferent from initial phase except in F. benjamina. N ratio decreased in first month and increases until late phase of incubation. C/N ratio increase in early phase then significantly decreasesuntil 3 months incubation. P ratio tends to decrease in first and third month. Ratio of polyphenol and Lignin decreases, however celluloses increase. The litter of four species has low chemical quality, respectively have low C/N ratio (< 25 %), lignin < 15 %, poliphenol < 3 % and (L+Pp)/ N > 8 %. Consequently, the litter tends to immobilize than mineralize. It effected to high ratio ofN such in L. speciosa. Decreasing and releasing of N in K. Africana showed that its nutrient transfer is better than in other species. P ratio quickly decreases in first 4 weeks of decomposition, it showed that P is not a limiting factors in species decomposition, relatively.Keywords : Litter, decomposition, percentage changes, nutrient